2005
DOI: 10.1109/tmi.2004.838324
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of noise-induced streak artifacts in X-ray computed tomography through spline-based penalized-likelihood sinogram smoothing

Abstract: We present a statistically principled sinogram smoothing approach for X-ray computed tomography (CT) with the intent of reducing noise-induced streak artifacts. These artifacts arise in CT when some subset of the transmission measurements capture relatively few photons because of high attenuation along the measurement lines. Attempts to reduce these artifacts have focused on the use of adaptive filters that strive to tailor the degree of smoothing to the local noise levels in the measurements. While these appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 25 publications
2
81
0
Order By: Relevance
“…Another parameter in the mean-variance model (15), i.e., the mean m e of the electronic noise, arising from the detector dark current, can be determined immediately before each scan by sampling the signals in those unexposed detectors over some time interval. 6,7,12 From Figs. 4 and 5, it can be observed that another parameter, i.e., the variance σ 2 e of the electronic noise, reduces slightly as the mAs value increases, and can be determined by the exponential relationship of Fig.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another parameter in the mean-variance model (15), i.e., the mean m e of the electronic noise, arising from the detector dark current, can be determined immediately before each scan by sampling the signals in those unexposed detectors over some time interval. 6,7,12 From Figs. 4 and 5, it can be observed that another parameter, i.e., the variance σ 2 e of the electronic noise, reduces slightly as the mAs value increases, and can be determined by the exponential relationship of Fig.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In practice, the variance σ 2 e of the electronic noise may be estimated from the sample variance of a series of dark current measurements. 6,7 Given the above four physical quantities, Eq. (15) provides a theoretical means to estimate the variance, which reflects the relative importance of each measurement for various data processing tasks, for example, a statistical image reconstruction task in the sinogram domain.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 3 more Smart Citations